Characteristics and transcriptomic analysis of scar tissues on the inner uterine cavity wall in patients with intrauterine adhesions - Li, Waixing; Gu, Pan; Gao, Bingsi; Zou, Lingxiao; Zhang, Aiqian; Huang, Huan; Zhao, Xingping; Xu, Dabao; Cheng, Chunxia (Frontiers in Physiology, 2022)
It has been previously reported that intrauterine adhesions (IUAs) are the main cause of uterine infertility. However, the histological origin of scar tissue present on the inner wall of the uterine cavity with IUAs has not been previously studied, which is particularly necessary for follow‐up research and prevention and treatment. In this study, myometrium with normal uterus were assigned to the control group and scar tissues with IUAs were assigned to the experimental group. And pathological characteristics and transcriptomic were analyzed between the two groups. We founded no difference was noted in the histological morphology and the α-SMA expression between the experimental and control groups. A total of 698 differentially expressed genes were identified between the two groups. Gene Ontology (GO) analyses revealed that the DEGs were significantly enriched in cell proliferation, AP-1 complex formation, and angiogenesis. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed that the target genes were significantly enriched in the AGE-RAGE, FOXO and TNF signaling pathway. This is the first study to propose that the scar tissues are mainly derived from the myometrium and the first one to report differentially expressed genes in the scar tissues of IUAs.